Greener production of compost from agricultural biomass residues amended with mule dung for agronomic application. (February 2022) - Sofia vizhimalar, A.; Vasanthy, M.; Thamaraiselvi, C.; Biruntha, Muniyandi; Paul, J. Arockia John; Thirupathi, Anand; Chang, Soon Woong; Xu, Zhi; Al-Rashed, Sarah; Munuswamy-Ramanujam, Ganesh; Ravindran, Balasubramani
Abstract: In this study agro-waste (Agwt) was aerobically composted using cow dung (CD) and mule dung (MD). Totally six different sets of compost treatments were prepared, as T1 (Agwt + CD, 1:1), T2 (Agwt + MD, 1:1), T3 (Agwt + CD, 1:3), T4 (Agwt + MD, 1:3), T5 (Agwt + CD, 3:1) and T6 (Agwt + MD, 3:1) in individual containers. All the compost treatments were degraded for 90 days. The organic wastes in the treatment containers were maintained with proper moisture level. All the final composts reached good manural stability and maturity index after 90 days. Among the six treatments, the T2 with Agwt + MD in 1:1 proportion attained a 10:1 C/N ratio and a near neutral pH (7.3). Indigenous microbes isolated and identified from the T2 compost sample showed protease, cellulase, amylase and lipase activities. The germination of Raphanus sativus L. seeds and vigorous plant growth parameters confirmed the non-pathogenic phytotoxic-free nature of finished composts. The radish crops supplied with T2 compost showed healthy tuber growth parameters (16.6 cm width, 35.6 cm length) compared with other treatments. The results from the experiments established that, the composts derived are eco-friendly amendment to plants and it has also improved the soil fertility due to its stability and maturity index. Thus, the present study concluded that composting agricultural crops waste with animal manure, especially mule dung promoted excellent biodegradation of organic complexes. It is a nature friendly solution for the management of solid waste such as agro-wastes utilizing mule dung. Graphical abstract: Image 1 Highlights: Equal parts of mule dung and agro waste (1:1, wt/wt) produced good quality compost. Isolated indigenous microbes had protease, amylase, cellulase and lipase activities. T2 final compost had pH 7.3, C/N ratio (10:1) after 90 days of aerobic degradation. Compost was non-phytotoxic with good manural stability and maturity index. Radish growth using T2 compost had good chlorophyll, vitamins and mineral values.